Beyond the Classroom: Exploring Teacher Loyalty in Vocational Education - Izzati, Umi Anugerah; Handayaningrum, Warih; Mulyana, Olievia Prabandini (Journal of Educational, Health and Community Psychology, 2024)
While extensive research has examined the relationship between gaming and aggression, few studies have focused on the factors that mediate the connection between trash-talking behavior and aggressive outcomes in multiplayer online battle arena (MOBA) games. This study addresses this gap by investigating the role of screen time as a mediator between trash-talking and aggressive behaviors in young players of Mobile Legends: Bang Bang (MLBB). Unlike previous research that primarily explored direct links between gaming and aggression, this study introduces screen time as a novel variable that influences this relationship. The study sampled 390 gamers aged 10 to 24 years, all enrolled at Southern Luzon State University in Lucban, Quezon, Philippines. Key variables, including verbal aggression, hostility, and anger, were assessed using standardized questionnaires, along with measures of trash-talking attitudes and screen time. Using mediation analysis, the study identified screen time as a key factor that explains the relationship between trash-talking and aggression. The findings revealed that trash-talking indirectly contributes to aggressive behavior through prolonged gaming exposure. In other words, the negative effects of trash-talking on aggression are amplified by increased screen time. This discovery offers a fresh perspective by highlighting screen time as a critical channel through which trash-talking influences aggression. The results underscore the importance of addressing both toxic communication and excessive screen time to foster a healthier and more sustainable gaming environment. As mobile gaming continues to dominate youth leisure activities, these findings provide actionable insights for developing interventions that reduce aggression and encourage positive competition in esports